Overcoming Barriers to Model Use - Shepherd, Simon; Koh, Andrew; Balijepalli, Chandra; Liu, Ronghui; Pfaffenbichler, Pauli; Emberger, Guenter; Ash, Andrew (European Journal of Transport and Infrastructure Research, 2009)
Research has shown that most local authorities do not use models in strategy formulation or scheme design and that others who do are doubtful of their value. This paper reports on a study aimed at enhancing analytical planning tools. Firstly, barriers to modelling of policy instruments were assessed by survey and literature review. From this themes for improving the modelling of demand restraint and public transport instruments were identified as areas of main concern along with ease of use and transparency of approach. Enhancements are reported for a range of existing models including strategic, macroscopic and micro-simulation techniques. Although these are demonstrated for specific software applications the methods are transferable to other models. Finally we consider to what extent the barriers have been addressed.